Analisis Kriminologis terhadap Fenomena Kejahatan Begal dengan Senjata Tajam di Kota Kendari - Kojongian, Rahayu; Anggriyani, Rima (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
Motorbike thieves in Kendari City are increasingly disturbing the public, they act without knowing the time or place. The intensity is also increasing sharply. However, there have been no preventative efforts carried out by the police on a large scale to ensure that Kendari is free from the